Efficacy of albendazole in combination with thymol against Echinococcus multilocularis protoscoleces and metacestodes - Albani, Clara Maria (2014)
The larval (metacestode) stage of the tapeworm Echinococcus multilocularis causes alveolar echinococcosis (AE), a mainly hepatic disease characterized by continuous asexual proliferation of metacestodes by exogenous budding, resulting in the tumor-like, infiltrative growth of the parasite lesion. Current chemotherapeutical treatment of AE relies on the use of benzimidazoles, albendazole (ABZ) and mebendazole, but these drugs act parasitostatic rather than parasitocidal, and due to their low success rate they imply a lifelong application causing severe side effects. Thymol is one of the major components of the essential oils of Thymus and is a widely known anti-microbial agent. The aim of the present work was to compare the efficacy of albendazole (ABZ) and thymol separately or combined on E. multilocularis protoscoleces and metacestodes. For this purpose, microscopical examinations at different time points were carried out. Moreover the tegumentary enzyme gamma glutamyl transferase (GGT) was measured to quantify the damage in metacestodes. Even though treatments of in vitro cultured E. multilocularis protoscoleces or metacestodes with ABZ or/and thymol showed that the drugs have an adverse effect on parasite viability, the combination of the two compounds at the concentration of 10 μg/ml showed the maximum anti-parasitic effect. Three days postincubation the first effects of the treatment were detected on protoscoleces and a marked reduction in viability (33%) was registered at day 18. Incubation of E. multilocularis metacestodes in the presence of ABZ 10 μg/ml + thymol 10 μg/ml during 10 days resulted in dramatic alterations such as strongly irregular and fissured surface and markedly disrupted vesicles. Scanning electron microscopy showed that protoscoleces as well as the germinal layer of E. multilocularis metacestodes were dramatically damaged following ABZ or/and thymol treatment. Also an important increase of tegumentary enzyme GGT was registered after 72 h postincubation with both drugs. The data reported in this article demonstrate a clear in vitro effect of ABZ + thymol against E. multilocularis protoscoleces and metacestodes.